A self-assembling keratin thermoplastic material and preparation method thereof

By placing keratin in a metal molten salt solution for self-assembly treatment, the problem of difficult processing of keratin raw materials into thermoplastics in the prior art is solved, and uniform modification and high performance stability of keratin thermoplastic materials are achieved, with high reuse rate and good water resistance of films.

CN118480194BActive Publication Date: 2025-03-21GUANGDONG VOCATIONAL & TECHNICAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410663472.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-03-21
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

It is difficult for the prior art to process keratin-rich raw materials into thermoplastics, and chemical modification and physical modification methods have problems such as uneven modification and poor performance stability.

Method used

By placing keratin in a metal molten salt solution for self-assembly treatment, hydrogen bonds between the alpha helix of the protein and the partial beta sheet are opened to form a thermoplastic material. The method includes three steps: pretreatment, crushing and self-assembly, and simple self-assembly using a metal molten salt solution to achieve regeneration of keratin and transformation of thermoplastic properties.

Benefits of technology

The uniform modification of keratin and the stability of product performance have been achieved. The melting point of keratin thermoplastic material is between 110°C and 180°C, the crystallinity is between 10% and 20%, and the reuse rate is close to 100%. There is no need to add common plasticizers, so the water resistance of the film has also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118480194B_ABST
    Figure CN118480194B_ABST
Patent Text Reader

Abstract

The present invention provides a self-assembling keratin thermoplastic material and a preparation method thereof, and belongs to the technical field of keratin self-assembly. The present invention pre-treats and removes impurities from a natural protein material rich in keratin, transfers the material to a metal molten salt solution after crushing, and obtains the self-assembling keratin thermoplastic material. The melting point of the self-assembling keratin thermoplastic material of the present invention is between 110°C and 180°C, the α-helix disappears in the protein material after self-assembly, and the crystallinity is between 10% and 20%. No plasticizer needs to be added when making the film, so the water resistance of the film will no longer be greatly reduced due to the transfer of the plasticizer, and the present invention can realize melt spinning and can be processed into consumables for 3D printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of keratin self-assembly, and in particular to a self-assembly keratin thermoplastic material and a preparation method thereof. Background Art

[0002] Synthetic fibers made from petroleum account for more than 80% of the global fiber consumption, but the production and use of synthetic fibers will cause a lot of pollutants to be discharged into the environment, while the acquisition of natural fibers represented by cotton fibers requires a lot of arable land. At the same time, with the development of the economy, the global consumption of poultry and livestock is increasing every year, but the large amount of keratin-rich substances such as animal hair and feathers are produced. The utilization of traditional keratin is achieved by dissolving it in an alkaline solution of urea and then using the dissolved part, resulting in some keratin losing its utilization value due to insolubility and becoming solid waste. The macromolecular structure of the above materials is rich in hydroxyl, amino, carboxyl, amide and other groups, and there are intermolecular forces such as van der Waals forces, hydrogen bonds, ionic bonds and disulfide bonds between them. The numerous forces between them make it impossible for them to exhibit the characteristics of thermoplasticity.

[0003] There are usually several methods to process the above keratin-rich raw materials into thermoplastics:

[0004] (1) Chemical modification: Add reducing agent / oxidizing agent / petroleum cracking monomer to rebuild the disulfide bonds in the protein or modify the hydrophobic groups. The disadvantage is that the oxidizing agent or reducing agent has no selectivity for the protein macromolecular chain, which greatly reduces the molecular weight of the protein, or because the modification occurs in a heterogeneous reaction, the protein modification reaction is uneven.

[0005] (2) Physical modification: Add plasticizers to reduce the interaction between protein macromolecular chains and increase the slippage between molecular chains. The disadvantage is that commonly used plasticizers are mostly alcohol substances, which have good solubility and are prone to reduce the performance of protein products in a wet environment.

[0006] Therefore, it is necessary to provide a method for treating keratin to make its modification uniform and improve the stability of product performance. Summary of the invention

[0007] In view of this, the present invention provides a method for preparing a self-assembled keratin thermoplastic material, wherein keratin is treated with a metal molten salt solution to obtain a regenerated keratin thermoplastic material, wherein the α-helix disappears in the self-assembled protein material and the crystallinity is between 10% and 20%.

[0008] The method for preparing the self-assembled keratin thermoplastic material of the present invention comprises the following steps:

[0009] (1) Pretreatment: The keratin-rich natural protein material is placed in an alkaline washing solution, then placed in an infrared heating device for heating treatment, washed with deionized water until neutral, and then placed in a vacuum oven for drying. This process mainly removes impurities such as soil, grease, and water-soluble components from the raw materials.

[0010] (2) Crushing keratin: crushing the dried natural protein material, sieving, and obtaining powdered keratin;

[0011] (3) Keratin self-assembly: The powdered keratin in step (2) is transferred to a metal molten salt solution for treatment, washed with distilled water, and then freeze-dried to obtain the self-assembled keratin thermoplastic material, and the washing liquid is recovered; this process mainly involves the reassembly of the keratin structure.

[0012] Preferably, the keratin-rich natural protein material in step (1) is selected from any one or more of poultry feathers and livestock hair, such as white chicken feathers, white duck feathers, white goose feathers, sheep wool, goat wool, camel wool, etc.

[0013] Preferably, the mass ratio of the natural protein material to the alkaline detergent in step (1) is 1:15-20. The alkaline detergent is composed of an alkaline detergent, a weak base and water; the weak base is sodium carbonate, and the concentration of the weak base in the alkaline detergent is 0.5 g / L-1 g / L; the alkaline detergent is a soap flake that is conventionally purchased on the market and does not contain fluorescence.

[0014] Preferably, the heating temperature in step (1) is 90° C. to 100° C., and the heating time is 50 minutes to 60 minutes.

[0015] Preferably, the drying temperature in step (1) is 80° C. to 90° C., and the drying time is 10 hours to 12 hours.

[0016] Preferably, the particle size of the powdered keratin in step (2) is less than 100 mesh.

[0017] Preferably, the metal molten salt solution in step (3) is any one of lithium bromide, zinc chloride and ferric chloride molten salt solutions, and the mass fraction of the metal molten salt in the metal molten salt solution is 50% to 60%. Even if heated to above the boiling point of water, no water in the metal molten salt solution will evaporate.

[0018] Preferably, the temperature of the metal molten salt solution treatment in step (3) is 20°C to 30°C, the treatment time is 20 to 30 minutes, and the rotation speed is 500 to 600 rpm.

[0019] Preferably, the freeze-drying temperature in step (3) is -50°C to -60°C, and the time is 10 hours to 12 hours.

[0020] Another object of the present invention is to provide a keratin thermoplastic material prepared by the above method.

[0021] The self-assembled keratin thermoplastic material prepared by the invention can be used for thermoforming, including hot pressing molding, melt spinning and FDM printing, and the thermoforming temperature is 140-180°C.

[0022] The present invention utilizes the strong electrophilicity of metal cations in the metal molten salt solution to easily open the hydrogen bonds between hydroxyl groups (-OH) and hydroxyl groups and the hydrogen bonds between hydroxyl groups (-OH) and carbonyl groups in the keratin α-helix and part of the β-folded layer. However, since the metal hydrated cations and non-metallic anions are not oxidizing and reducing, they cannot open the disulfide bonds (-SS-) in the keratin molecular structure, so that the regenerated keratin is converted from a thermosetting material to a thermoplastic material. Since the α-helix and part of the β-folded layer of the keratin are opened, the keratin will not be completely dissolved in the metal molten salt like silk fibroin and cellulose, but will self-assemble and aggregate into clusters, so that the regenerated keratin can also be easily separated from the metal salt aqueous solution, and the thermoplastic keratin can be processed into a certain product form by heating.

[0023] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a self-assembling keratin thermoplastic material and a preparation method thereof, using a natural protein material rich in keratin as a raw material, the content of sulfur-containing amino acids (such as cystine, cysteine, and methionine) is between 5% and 20%, and then using a metal molten salt for simple self-assembly, the melting point of the keratin thermoplastic material is between 110°C and 180°C, the α-helix disappears in the protein material after self-assembly, and the crystallinity is between 10% and 20%. And by using the rapid self-assembly of keratin powder into balls in a metal molten salt solution, the keratin recycling rate is close to 100%.

[0024] When the self-assembled keratin thermoplastic material of the present invention is used to make a film, it is not necessary to add common plasticizers, such as glycerol, ethylene glycol, tributyl citrate, etc., so the water resistance of the film will no longer be greatly reduced due to the transfer of the plasticizer.

[0025] Traditional protein spinning utilizes solution spinning, but the present invention can realize melt spinning and process it into consumables for 3D printing. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A transparent film prepared by hot pressing the powdered self-assembled keratin thermoplastic material at 140° C. in Example 1;

[0027] Figure 2The differential thermal analysis results of the thin films prepared from the powdered keratin and the powdered self-assembled keratin thermoplastic material in Example 1;

[0028] Figure 3 The Raman spectra of the films prepared from the powdered keratin and the self-assembled keratin thermoplastic material in Example 1;

[0029] Figure 4 The crystallization changes characterized by X-ray diffraction of thin films prepared from powdered keratin and self-assembled keratin thermoplastic materials in Example 1;

[0030] Figure 5 The state of the keratin filaments prepared by the self-assembled keratin thermoplastic material at 140° C. under a microscope (100 times);

[0031] Figure 6 This is a finished product image of the self-assembled keratin thermoplastic material 3D printed in Example 1;

[0032] Figure 7 This is a state diagram of the powdered keratin after hot pressing at 140° C. in Example 1;

[0033] Figure 8 This is a state diagram of the powdered self-assembled keratin thermoplastic material in Example 1 after hot pressing at 120°C. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] A method for preparing a self-assembled keratin thermoplastic material, comprising the following steps:

[0037] (1) Pretreatment: Take 20 g of chicken feathers of mature white-feathered chickens and place them in a stainless steel cup containing alkaline detergent, wherein the mass ratio of the chicken feathers to the alkaline detergent is 1:20, and the alkaline detergent contains 1 g / L of non-fluorescent soap flakes (the soap flakes are conventional products purchased on the market) and 0.5 g / L of sodium carbonate;

[0038] Then the stainless steel cup is transferred to a rotatable infrared heating device and treated at 95°C for 60 minutes. After the treatment, it is washed with distilled water until the pH value of the washing liquid is neutral; the impurity-free chicken feathers are then transferred to a vacuum oven at 80°C for 12 hours. This process mainly involves the impurity removal of raw materials to remove impurities such as soil, grease, and water-soluble components.

[0039] (2) Crushing of keratin: After drying, the chicken feathers are cut with scissors to a length of 0.5 to 1 cm, and then crushed and sieved in a powder grinder to obtain powdered keratin (powdered chicken feather particles) with a particle size of less than 100 mesh;

[0040] (3) Keratin self-assembly: Take 5g of the above powdered keratin and transfer it to a 60% by mass lithium bromide molten salt aqueous solution for self-assembly treatment, with a stirring speed of 500 rpm, a treatment temperature of 25°C, and a treatment time of 30 min. After the treatment, the powdered keratin will be assembled into keratin spheres, which are taken out of the solution, washed with distilled water for 5 times, and then transferred to a freeze dryer for drying at -60°C for 12 hours to obtain the self-assembled keratin thermoplastic material.

[0041] The self-assembled keratin thermoplastic material prepared by the present invention is weighed, and the keratin recovery rate is calculated to reach 99.9%. The distilled water washing liquid and the lithium bromide treatment liquid are distilled to obtain lithium bromide solid powder, which is reused for the next chicken feather powder treatment.

[0042] The self-assembled keratin thermoplastic material in step (3) of Example 1 was placed in a powder grinder for secondary crushing, and a 100-mesh sieve was used to screen the powdered self-assembled keratin thermoplastic material with a particle size less than 100 mesh. The following experiment was performed:

[0043] Experiment 1: 3 g of powdered keratin (powdered chicken feather particles prepared in step (2) without self-assembly) and powdered self-assembled keratin thermoplastic material (material obtained after self-assembly in step (3)) were respectively placed in a mold, and hot-pressed for 10 min at 140° C. and 10 MPa on a hot press. Then, cooling water was passed through the mold. After the temperature dropped to room temperature, a transparent film was prepared. Figure 1 .

[0044] 2 g of the dried film was placed in distilled water with a pH value of 6.5 for 48 hours, and the weight loss rate of the dried film was less than 0.5%, which shows that the film of the present invention has good water resistance.

[0045] Then, the powdered keratin and the films made of powdered self-assembled keratin thermoplastic materials were subjected to differential thermal analysis (DSC) to characterize the changes in the melting points of the powdered keratin films and the self-assembled keratin films. Figure 2 ,from Figure 2 It can be seen that simply crushed powdered keratin does not show a melting point, while the melting point of the self-assembled keratin thermoplastic material is 132°C.

[0046] Raman spectroscopy was used to characterize the changes in disulfide bonds in films made of powdered keratin and self-assembled keratin thermoplastic materials. Figure 3 .from Figure 3 It can be found that the areas between the two are basically the same, so the disulfide bonds of keratin after self-assembly in the metal molten salt solution are basically not destroyed.

[0047] The changes in crystallinity of powdered keratin and self-assembled keratin thermoplastic films were characterized by X-ray diffraction. Figure 4 (XRD spectrum). Figure 4 It can be seen that the α-helix and β-folded structure of the powdered keratin at about 9° disappeared after the self-assembled particles. This is because the content of α-helix and β-folded structure at about 9° is low, and the α-helix is ​​extremely unstable. It is easily destroyed when encountering aggressive molten salt metal ions. The β-folded structure at about 9° is a pure layered structure with more hydrogen bonds between layers. At the same time, the present invention uses a short-term treatment at room temperature, which has limited damage to the β-folded structure. In short, before and after the molten salt self-assembly treatment, the crystallinity dropped from 36 to 15.

[0048] Experiment 2

[0049] 10 g of the secondary crushed self-assembled keratin thermoplastic material was added to a twin-screw extruder, wherein the machine temperature was 140°C and the screw speed was 50 rpm. The state of the prepared keratin filaments under a microscope (100 times) was as follows: Figure 5 As shown. Figure 5 It can be seen that its diameter is 13μm and its outer surface is relatively smooth.

[0050] Experiment 3

[0051] 10g of the secondary crushed self-assembled keratin powder was added to a twin-screw extruder at a machine temperature of 140°C and a screw speed of 10 rpm to form a wire with a diameter of 1.5mm. The wire was then placed in a 3D printer to print the designed pattern. The printer head temperature was set to 138°C. The printed product can be seen in Figure 6 .

[0052] Experiment 4

[0053] Directly take 3g of the powdered keratin (powdered chicken feather particles) prepared in step (2) and put it into a mold. After hot pressing for 10 minutes at 140°C and 10 MPa, the state after hot pressing is shown in FIG. Figure 7 .from Figure 7 It can be found that the crushed chicken feather keratin cannot form a film without molten salt treatment. This is because keratin has a strong intermolecular force, so it is a thermosetting material.

[0054] Experiment 5

[0055] According to the content of Experiment 1, the hot pressing temperature was changed to 120℃, and other parameters remained unchanged. The state of the film after hot pressing is shown in Figure 8 As shown, from Figure 8 It can be seen that the self-assembled keratin did not form a complete film due to the insufficient hot pressing temperature.

[0056] Example 2

[0057] A method for preparing a self-assembled keratin thermoplastic material, the steps are the same as those in Example 1, except that the raw material in Example 2 is sheep wool. The melting point of the self-assembled keratin finally prepared is 164°C.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a self-assembled keratin thermoplastic material, characterized in that: The following steps are involved: (1) Pretreatment: The keratin-rich natural protein material is placed in an alkaline detergent, then placed in an infrared heating device for heating, washed with deionized water until neutral, and then placed in a vacuum oven for drying; (2) Crushing of keratin: crushing the dried natural protein material, sieving it, and obtaining powdered keratin; (3) Keratin self-assembly: the powdered keratin obtained in step (2) is transferred to a metal molten salt solution for treatment, washed with distilled water, and then freeze-dried to obtain the self-assembled keratin thermoplastic material, and the washing liquid is recovered; In step (1), the mass ratio of the natural protein material to the alkaline washing liquid is 1:15-20; the alkaline washing liquid is composed of an alkaline detergent, a weak base and water; the weak base is sodium carbonate, and the concentration of the weak base in the alkaline washing liquid is 0.5 g / L-1 g / L; The heating temperature in step (1) is 90°C to 100°C, and the time is 50 minutes to 60 minutes; the drying temperature in step (1) is 80°C to 90°C, and the time is 10 hours to 12 hours; The metal molten salt solution in step (3) is any one of lithium bromide, zinc chloride and ferric chloride molten salt solutions, and the mass fraction of the metal molten salt in the metal molten salt solution is 50% to 60%; The temperature of the metal molten salt solution treatment in step (3) is 20°C to 30°C, the treatment time is 20 to 30 minutes, and the rotation speed is 500 to 600 rpm; the freeze-drying temperature in step (3) is -50°C to -60°C, and the time is 10 hours to 12 hours.

2. The method for preparing the self-assembled keratin thermoplastic material according to claim 1, characterized in that: The keratin-rich natural protein material in step (1) is selected from any one or more of poultry feathers and livestock hair.

3. The method for preparing the self-assembled keratin thermoplastic material according to claim 1, characterized in that: The particle size of the powdered keratin in step (2) is less than 100 mesh.

4. A self-assembled keratin thermoplastic material, characterized in that: The self-assembled keratin thermoplastic material is prepared according to the method for preparing the self-assembled keratin thermoplastic material according to any one of claims 1 to 3.

5. The use of the self-assembled keratin thermoplastic material according to claim 4, characterized in that: The keratin thermoplastic material can be used for thermoforming, and the thermoforming includes hot pressing, melt spinning, and FDM printing. The thermoforming temperature is 140-180°C.